Characteristics of the natural flow regime paradigm explain occurrence of imperiled Great Plains fishes. Issue 9 (5th September 2021) - Nguyen, Erin; Perkin, Joshuah S.; Smith, Ryan; Mayes, Kevin B.; Trungale, Joe
Abstract: The natural flow regime (NFR) paradigm posits that naturally occurring temporal fluctuations in streamflow are necessary for maintaining natural ecological communities. Conservation actions guided by the paradigm have contributed to stream organism conservation on a global scale, yet NFR applications in highly altered Great Plains streams are lacking. We analyzed historical (1980–2017) fish occurrence and flow data from sixteen gage locations across three Great Plains river basins with the goal of relating flow indices calculated for one year prior to each fish collection with the occurrence of fishes belonging to the highly imperiled pelagic‐broadcast spawning (PBS) reproductive guild. We fit random forest models using flow indices, gage identification, and watershed area as predictor variables and PBS fish occurrence as the response variable for all suspected or confirmed PBS fishes in each basin. Results revealed that flow indices from all NFR characteristics were useful for predicting PBS fish occurrence, but the identity of the most important flow indices varied by species and river basin. We also found that gage location was an important predictor variable, indicating flow–ecology relationships are spatially contingent and suggesting the influence of other factors that vary spatially (e.g., river fragmentation and water quality). Partial dependence plots identified thresholds in flow indices such as the timing of maximum flows and fall rate that may be associated with the presence or absence of PBS fishes, and these plots can be used to identify flow index target values to benefit conservation efforts. Time series predictions for likelihood of occurrence at a single gage in the Brazos River basin revealed a positive correlation between likelihood of occurrence and non‐drought years for three of four species present, supporting recent findings that drought suppresses PBS fish populations. This study provides insight into the flow requirements of some of the most imperiled stream fishes in North America and contributes to environmental flow science on a global scale by establishing a robust methodology for delineating flow–ecology relationships.